Criminology in Post-Violence Transitions - Ailsa Peate; Natalia Maystorovich Chulio; Camilo Tamayo Gómez (International Journal for Crime, Justice and Social Democracy)
As guest editors, we situate this issue at the nexus of criminology and transitional justice. We argue that criminology, with its insights into the causes of violence, the operation of justice systems, and the experiences of victims and survivors, has much to offer to the study of post-conflict societies. Conversely, engaging with transitional contexts pushes criminology beyond its traditional bounds, demanding interdisciplinary approaches and a willingness to centre voices and epistemologies often marginalised in mainstream discourse. The contributions in this issue span diverse geographical regions and cultural contexts, with a particular focus on the Global South. Case studies range from Latin America (Guatemala, Colombia, Chile, Argentina) and Africa (The Gambia, Nigeria, Cameroon, South Africa) to Europe (Spain) and international justice fora (the International Criminal Court). Each article reflects unique local realities, from Indigenous struggles in Colombia and Guatemala to post-authoritarian memory struggles in Spain, Argentina, and The Gambia, while collectively speaking to universal themes of justice, accountability and healing after violence.